(untitled) (Zoo Botanica, 2025)
The present study investigates the biochemical composition and antioxidant activity of indigenous and exotic apple varieties (Malus domestica Borkh.) grown in the Baltistan region of Pakistan. Two local varieties, Saspolo and Kachura Ambari, along with two exotic varieties, Five Star and Golden Delicious, were analyzed for primary and secondary metabolites, including proteins, carbohydrates, phenols, flavonoids, tannins, and alkaloids. Quantitative analysis revealed significant differences (P < 0.001) in total phenolic content (TPC) and total flavonoid content (TFC) among the studied varieties. The highest TPC was recorded in the peel of Saspolo apple (41.59 ± 0.11 mg GAE/100 g), while the flesh of Five Star showed the highest TPC (43.71 ± 0.05 mg GAE/100 g). Antioxidant activity, assessed using the DPPH radical scavenging assay, demonstrated maximum activity in Saspolo variety (82.42% ± SD) at the tested concentration (100 µg/mL). The results indicated substantial biochemical diversity among apple varieties from Baltistan, with native cultivars exhibiting superior antioxidant potential, particularly in the peel. These findings highlight the nutritional and functional importance of native apple germplasm adapted to high-altitude agro-climatic conditions in mountain areas of Gilgit-Baltistan, Pakistan.